Jordanian woman leadership of public sector: Personality as a barrier to their success - Ahmad, Fais; Faraj Zubaidi, Faraj Radzuan (2013)
It is essential for us to have a deep understanding of the working woman issue and the magnificent task which working women have in developing and strengthening the society.The leadership of woman is a valuable step in the society developing process.The study used questionnaire to collect the data from participants who are female Jordanian working in the public sector. This study used Statistical Package for Social Science (SPSS) to quantify and analyze the collected data through survey questionnaire.The goal of this study is to disclose the obstacles and the difficulties faced by Jordanian working women in achieving the leadership position due to the discrimination that seems to be rampant in the public sector.Apart from that, it is also aims to find out whether the provision of training can help in overcoming this predicament.This phenomenon might relate to the personality of Jordanian women which might cause male leader to deprive women from moving upward in the organization. Accordingly, this research indicates that Jordanian women are always been inferior with regard to leadership and decision-making positions.In addition, inequality between men and women seems to be continuously existed, making it difficult for women to ascend to leadership positions.